Incremental diagnostic value of epicardial adipose tissue for the detection of functionally relevant coronary artery disease. Issue 1 (September 2015) - Romijn, M.A.; Danad, I.; Bakkum, M.J.; Stuijfzand, W.J.; Tulevski, I.I.; Somsen, G.A.; Lammertsma, A.A.; van Kuijk, C.; van de Ven, P.M.; Min, J.K.; Leipsic, J.; van Rossum, A.C.; et al.
Abstract Background and Aim To determine the incremental diagnostic value of epicardial adipose tissue (EAT) volume in addition to the coronary artery calcium (CAC) score for detecting hemodynamic significant coronary artery disease (CAD). Methods and Results 122 patients (mean age 61 ± 10 years, 61% male) without a previous cardiac history underwent a non-contrast CT scan for calcium scoring and EAT volume measurements. Subsequently all patients underwent invasive coronary angiography (ICA) in conjunction with fractional flow reserve (FFR) measurements. A stenosis >90% and/or a FFR ≤0.80 were considered significant. Mean EAT volume and CACscore were 128 ± 51 cm3 and 418 ± 704, respectively. The correlation between EAT volume and the CACscore was poor (r = 0.11, p = 0.24). Male gender (odds ratio [OR] 2.86, p = 0.01), CACscore ([cut-off value 100] OR 3.31, p = 0.003, and EAT volume ([cut-off value 92 cm3] OR 4.28, p = 0.01) were associated with flow-limiting disease. The multivariate model revealed that only male gender (OR 2.50, p = 0.045), CAC score (OR 3.60, p = 0.005), and EAT volume (OR 4.95, p = 0.02) were independent predictors of myocardial ischemia. Using the cut-off values of 100 (CAC score) and 92 cm3 (EAT volume), sensitivity, specificity, negative predictive value, positive predictive value, and accuracy for detecting functionally relevant CAD as indicated by FFR were 71, 57, 77, 50 and 63% and 91, 29, 85, 44 and 52% for the CACscore and EAT volume, respectively. Adding EAT volume to the CAC score and cardiovascular risk factors did not enhance diagnostic performance for the detection of significant CAD (p = 0.57). Conclusion EAT volume measurements have no diagnostic value beyond calcium scoring and cardiovascular risk factors in the detection of hemodynamic significant CAD.